1980
DOI: 10.3109/01480548009108283
|View full text |Cite
|
Sign up to set email alerts
|

Toxicologic Evaluation of Streptozotocin (NSC 85998) in Mice, Dogs and Monkeys

Abstract: Single intravenous doses of CDF1 mice, and single and five daily intravenous treatment schedules in beagle dogs and rhesus monkeys were used to evaluate the toxicity of Streptozotocin (SZN). The major target organs in the three species were liver, kidney, lymphoid tissue and pancreatic islet beta cells. Moderate bone marrow depression and gastrointestinal toxicity were observed in the large animal species after lethal doses. Monkeys were less sensitive than the dog to the hepatotoxic effects of SZN and clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

1984
1984
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 4 publications
2
29
1
Order By: Relevance
“…Diabetes induction using other non-STZ agents, e.g., diphtheria toxin in rat insulin promoter diphtheria toxin receptor (RIP-DTR) transgenic mice, has been associated with a reduction in leukocytes and splenocytes. 16 STZ-induced changes in the haematopoietic and reticuloendothelial systems of mice, dogs, and monkeys were documented by Levine et al 18 The maximum dose of STZ used on monkeys in their study was 80 mg/kg, which is less than that used in most nonhuman primate islet transplant models. The median lethal dose of STZ for monkeys in Levine's study (80 mg/kg) was found to cause necrosis of lymphoid tissue, bone marrow hypoplasia, anemia, and neutrophilia.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Diabetes induction using other non-STZ agents, e.g., diphtheria toxin in rat insulin promoter diphtheria toxin receptor (RIP-DTR) transgenic mice, has been associated with a reduction in leukocytes and splenocytes. 16 STZ-induced changes in the haematopoietic and reticuloendothelial systems of mice, dogs, and monkeys were documented by Levine et al 18 The maximum dose of STZ used on monkeys in their study was 80 mg/kg, which is less than that used in most nonhuman primate islet transplant models. The median lethal dose of STZ for monkeys in Levine's study (80 mg/kg) was found to cause necrosis of lymphoid tissue, bone marrow hypoplasia, anemia, and neutrophilia.…”
Section: Discussionmentioning
confidence: 88%
“…17 Levine et al studied the toxicological effects of STZ in mice and in large animals (dogs and rhesus monkeys), and reported necrosis of lymphoid organs, and bone marrow hypoplasia. 18 The present report consists of our observations in cynomolgus monkeys.…”
Section: Introductionmentioning
confidence: 93%
“…STZ treatment had little effect on AdipoR1/R2 mRNA levels in the liver, whereas insulin significantly decreased the AdipoR1/R2 mRNA levels in the liver of STZ-treated mice (data not shown). These results may be explained by the observations that inflammation may decrease AdipoR1/R2 mRNA levels 2 and that STZ treatment may induce inflammation in the liver (23).…”
Section: Fasting Increased But Refeeding Decreased Adipor1/r2mentioning
confidence: 78%
“…However, it is also known that SZ has acute toxic effects on many organs in some animal species (Levine et al, 1980) and leads to delayed-type renal toxicity in rats (Rakieten et al, 1968;Okawa & Doi, 1983). This suggests that full attention should be paid to histopathological changes in other organs as well as the pancreas when SZ-treated animals are used for studies on diabetes.…”
Section: Abstract: Mice; Streptozotocin; Diabetes Mellitus Experimenmentioning
confidence: 99%